Geographical variability of Lepyronia coleoptrata (Linnaeus, 1758) (Hemiptera: Cercopoidea) across Russia - Tishechkin, Dmitri Yu. (Zootaxa, 2019)
Comparative analysis of body size, coloration, penis shape, and male calling signals of Lepyronia coleoptrata from different localities in European Russia, Northern Kazakhstan, Siberia, and the Russian Far East showed that all populations studied belong to the same species. A clear boundary between European and the Far-Eastern subspecies can only be drawn based on body size and proportions. Light coloration is typical of European populations; on the contrary, in the Far East only dark specimens occur, but in Siberia a mixture of different forms presents. Penis shape and male calling signal pattern do not demonstrate geographical variability. The range of intraspecific variability of these traits is far less than interspecific differences between L. coleoptrata, L. koreana, and L. okadae.